TREM1 fosters an immunosuppressive tumor microenvironment in papillary thyroid cancer. Issue 2 (10th January 2022) - Zhao, Yang; Zhang, Cangang; Zhu, Yanan; Ding, Xi; Zhou, Yikun; Lv, Hongjun; Lin, Yuxuan; Wu, Yuan; Shi, Bingyin; Fu, Jiao
Abstract : The immunosuppressive microenvironment is associated with poor prognosis in papillary thyroid cancer (PTC); however, the molecular mechanisms involved are unknown. Among the triggering receptors expressed on myeloid cell (TREM) family, we found that TREM1 expression in PTC was significantly higher than that in normal tissues. TREM1 overexpression was associated with BRAF V600E profiles and advanced tumor stages. Furthermore, TREM1 mRNA expression was negatively correlated with promoter methylation status. Specifically, hypomethylation of CpG site cg06196379 in the TREM1 promoter was related with poor patient disease-free survival (DFS) and a high PTC recurrence rate. Mechanistically, TREM1 was mainly expressed in malignant epithelial cells but not in macrophages in PTC by single-cell analysis. PTC tissues with high TREM1 levels had enhanced infiltration of regulatory T cells (Tregs) and decreased infiltration of CD8+ T cells. Our study confirms that hypomethylation-mediated overexpression of TREM1 in PTC cells promotes an immunosuppressive microenvironment by enhancing Treg infiltration. We recommend the future use of therapeutic strategy targeting TREM1 for the treatment of PTC.